Benefits and Risks of Using Blockchain in Smart Energy: A Literature Review - Erturk, Emre; Lopez, Dobrila; Yu, Wei Yang (Contemporary Management Research, 2020)
Being a decentralized system makes Blockchain a suitable technology solution in many cases. The Smart Energy domain has the potential to benefit from the use of Blockchain, by improving data and transaction management, through applications such as peer-to-peer energy trading, grid enhancement, and electric vehicle support. Many researchers have proposed models and prototypes of blockchain-based applications, which are expected to improve the performance of smart energy systems. In this report, a qualitative literature review was performed to look into a sample of these application proposals and to try to identify the impacts of blockchain technology in Smart Energy. This resulted in the discovery of both positive and negative factors. The beneficial factors include increased security, improved data privacy, data transparency and immutability, removal of third-party control and trust, ubiquitous solution, and greater data accessibility. The list of challenges includes limited scalability and speed, off-chain support requirement, high establishment and maintenance cost, and requiring further practical tests. One of the interesting findings is that the impact of Blockchain technology as to whether it may increase or decrease transaction costs is still unclear. Finally, the paper recommends that a future study may focus on economic feasibility and transaction costs, and ascertain which Smart Energy cases and application designs are more appropriate for Blockchain technology.